Noves consideracions al voltant de Bernat Fenollar, domer de la Seu de València. - APARISI, FREDERIC (Scripta, 2021)
Bernat Fenollar has attracted the attention of literature historians for his involvement in the literary development of Valencia in the second half of the fourteenth century and for his own literary works. The interest of socioeconomic and ecclesiastical historians has been more unusual. This work focuses indeed on these two perspectives, the socio-economic and the ecclesiastical, to revise the personal and professional trajectory of the domer de la Seu. Therefore, issues related to the literary field are left out. For the achieving all this, the ecclesiastical records from the Arxiu de la Catedral de València have been used, but above all notarial records from four archieves, that is, the said Cathedral, the Arxiu del Regne de València, the Arxiu de Protocols del Col·legi Corpus Christi College de València and Arxiu Parroquial de Penàguila. This has made it possible to outline his kinship and his family relationships, his sources of income, which went beyond his remuneration as a clergyman and his work in the administration of the cathedral, and to suggest a possible date for his death.